Modernizing Myth : A Comparative Analysis of Traditional Legends in the Ne Zha Animated Film Series - Qin, Huimin; Tirakoat, Suwich (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2025)
In recent years, the adaptation of mythological themes in audiovisual media has expanded significantly. However, existing research often focuses on case studies or broad paradigms, lacking a systematic exploration of the interactions between technological aesthetics, ideology, and mythic narratives. This article examines the animated films “Ne Zha” and “Ne Zha 2,” using a three-dimensional analytical framework of “cultural deconstruction—technological empowerment—value reconstruction” to explore the modern translation strategies of the Ne Zha character and its socio-cultural implications. Through text comparison and key scene interpretation, the study compares the films' narrative themes, character identities, visual symbols, and ideological expressions. It reveals that Ne Zha's image has shifted from “individual resistance” to “collective action,” with the narrative focus expanding from individual struggles against social prejudice to collective resistance against systemic oppression. This evolution is achieved through cyberpunk aesthetics and fluid simulation technologies, reshaping traditional mythological symbols and positioning animated films as a medium for critical cultural reproduction. The paper also discusses the balancing strategies used by Chinese animated films between traditional symbols and contemporary expression, offering a new theoretical framework for modernizing mythological intellectual properties (IPs).